Pengaruh Moderasi Beragama dan Keaktifan Majelis Taklim terhadap Internalisasi Nilai-nilai Keagamaan di Desa Patihan Kidul, Siman, Ponorogo: Influence of Religious Moderation and Majelis Taklim Participation on the Internalization of Religious Values in Patihan Kidul Village, Siman, Ponorogo - Rajendra Nur Pallasta; Megan Wicaksono; Candra Dhiyaul Hisyam (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Indonesia is known as a country rich in religious diversity, with Islam as the majority religion practiced by the majority of the population. This diversity includes not only religion, but also ethnicity, culture, and local traditions that live side by side in one nation. The research used is a quantitative research type with the aim of this research is to determine whether there is an influence and the magnitude of the influence of the role of understanding religious moderation and the activeness of the taklim assembly on the internalization of religious values ​​in Patihan Kidul Village, Siman District, Ponorogo Regency. This research is a study that has a total population of 30 respondents with a quantitative approach to the survey model. The main instrument for data collection is using a questionnaire. Data that meets and passes the validity and reliability test, the classical assumption test, are then analyzed using the F test in multiple linear regression using the IBM SPSS Statistics 23 program which produces the following equation: Ŷ = 3.360 + 0.382 + 0.393. The results show that F count 19.269 > F table 3.30 df = 2; df2 = 31 at a 5% significance level, indicating that religious moderation and the Islamic study group simultaneously influence internalization. An R Square of 0.554 indicates that the religious moderation and Islamic study group variables contribute 55.4% to the internalization variable. The remainder is influenced by other variables not included in the study. The R Square value of 55.4% can be classified as having a moderate influence on the dependent variable based on Chin's theory.